Knowledge Regarding Impact of Social Media Use Among Nursing Students - Bansal, Satish Chand; Kaur, Khushpreet; Kaur, Masprabhsimerpreet; (GS), Kamaljeet Kaur; Kaur, Karanveer; Kaur, Khushpreet (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2023)
Introduction: This research aimed to find out the level of knowledge of nursing students regarding social media impact and to determine how they are using their knowledge regarding social media in their daily life practices. This study’s primary objective was to rule out students’ social media usage goals and educational perspectives. Methodology: A non-experimental descriptive search method was employed. A non-probability sampling technique was used for the selection of 50 nursing students (17-22 yrs.) study in selected nursing colleges in Sri Muktsar Sahib district of Punjab. In this study, a self-structured knowledge questionnaire and practice checklist has been prepared to assess the knowledge and practices of nursing students regarding the impact of social media use on their lives. Results: Descriptive and inferential statistics were used to analyse the data collected, and the results showed that out of 50 nursing students, 3 (6%) had good knowledge scores, 45 (90%) had average knowledge scores, and 2 (4%) had poor knowledge scores regarding the effects of social media use. The findings also showed that 24% of nursing students had satisfactory practice scores and 76% of them had unsatisfactory practice scores when it came to using social media. Conclusion: The majority of nursing students had an average knowledge score regarding the effect of social media use, according to the conclusions drawn from the data analysis. The findings also indicated that the majority of nursing students’ practice scores for the influence of social media use were subpar.